Improving Digital Health Information Literacy for Adolescents through Search Engine Optimization - Gusti Ayu Oviani; I Gede Bagus Indra Marangyana; Ni Luh Gde Mona Monika; Ella Yunita (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Internet use is increasing every year, most of the reason is finding information (80.1%). Along with this, misinformation is circulating, including health information, so digital literacy is needed, especially for teenagers or Generation Z who are technology savvy. This activity aims to increase teenagers' digital literacy and help them search for appropriate health information through search engines. This Community Service is carried out using the Participatory Action Research (PAR) method with direct face-to-face presentation of material and practice on the given topic. Participants were 43 high school/equivalent level students aged 15-19 years. Most participants were 16 years old (46.51%) and female (88.37%). The average knowledge of participants regarding appropriate health information in the pre-test was 60.21, and the post-test was 88.65. A total of 40 out of 43 participants experienced an increase in scores (93.02%) after lectures and practice. This activity concluded that participants' knowledge and skills increased regarding using search engines to manage appropriate health information.